Association of gut microbiota with obesity in children and adolescents - Ky Young Cho (The Korean Pediatric Society, 2023)
Pediatric obesity is among the most serious global health problems whose prevalence has increased over the past decade. Pediatric obesity increases concomitant health problems, including type 2 diabetes mellitus, hypertension, dyslipidemia, fatty liver disease, and psychological problems, which often progress into adulthood. The gut microbiota is a new factor in the development of obesity, which is affected by renowned risk factors such as diet, lifestyle, and socioeconomic status. This review aimed to describe the association between the gut microbiota and childhood obesity. According to advances in gene sequencing technologies, many findings of experimental animal and human studies of adults and children demonstrated that compositional and functional changes in the gut microbiota (dysbiosis) are associated with the development of obesity. Many studies have reported that an increased Firmicutes/Bacteroidetes (F/B) ratio is a biomarker of obesity susceptibility; however, with the rapid accumulation of data, meta-analyses of human gut microbiota and obesity showed no clear association between F/B ratio and obesity status. The contribution of the microbiota to obesity has been considered using multifactorial approaches, such as supplying additional calories to the host, modulating blood lipopolysaccharide levels, favoring fat storage, and affecting satiety. Probiotics are proposed to manipulate the gut microbiota population to improve obesity; however, their clinical application remains limited because trials have shown different results. Further studies are required to better understand the mechanisms underlying the observed association between the gut microbiota and pediatric obesity.